2022
DOI: 10.1007/s00464-021-08958-1
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of virtual reality endoscopy training to live animal colonoscopy: a randomized control trial of proficiency vs. repetition-based training

Abstract: Background Low first-time pass rates of the Fundamentals of Endoscopic Surgery (FES) exam stimulated development of virtual reality (VR) simulation curricula for test preparation. This study evaluates the transfer of VR endoscopy training to live porcine endoscopy performance and compares the relative effectiveness of a proficiency-based vs repetition-based VR training curriculum. Methods Novice endoscopists completed pretesting including the FES manual skills examination and Global Assessment of GI Endoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Cassidy et al (2022) [ 37 ] studied the effect of VR training on real endoscopic surgical outcomes in the porcine model. They used a virtual reality endoscopic simulator (GI Mentor; 3D Systems, Rock Hill, SC, USA) in their study on colonoscopy training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cassidy et al (2022) [ 37 ] studied the effect of VR training on real endoscopic surgical outcomes in the porcine model. They used a virtual reality endoscopic simulator (GI Mentor; 3D Systems, Rock Hill, SC, USA) in their study on colonoscopy training.…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles we included in our review, 11 and 13 studies were based on VR and AR, respectively. Among the VR studies, one of them was based on non-immersive VR and was performed using a monitor or a screen [ 52 ], four articles were based on semi-immersive VR [ 34 , 35 , 36 , 37 ], and six of them were based on full-immersive VR [ 3 , 12 , 39 , 46 , 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling the biomechanics of the living organism is crucial for the acceptance of ex vivo simulators [35]. They have been evaluated and thoroughly tested, including a randomized controlled trial, and found to be helpful in gaining experience, training, and even proficiency, irrespective of the level of experience at the start of the training [32,78]. Trainees and even advanced and experienced endoscopists felt that they gained additional experience and proficiency from using ex vivo simulators, especially if they were using them in a structured manner [79].…”
Section: Discussionmentioning
confidence: 99%